Dukungan keluarga (etnis Batak Toba) terhadap kepatuhan lansia penderita hipertensi dalam menjalani pengobatan - Sirait, Trisno; Nasution, Siti Zahara; Siregar, Farida Linda Sari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2024)
Background: Hypertension is a disorder of the blood vessels that causes the supply of oxygen and nutrients carried by the blood to be blocked to the body tissues that need it. Family support is the attitude, actions, and acceptance of the family towards their family members in the form of emotional support, instrumental support, informational support, and appreciation support. Purpose: To analyze family support (Batak Toba ethnic group) towards the compliance of elderly hypertension patients in undergoing treatment. Method: Quantitative research with a cross-sectional approach was conducted in the Batak Toba community in the working area of ​​the Uluan Health Center technical implementation unit as many as 64 patients and Janji Matogu as many as 76 patients in February-March 2024 as many as 140 samples. Data collection used a non-probability sampling technique, namely purposive sampling and the Slovin formula for a 5% error rate. The sample inclusion criteria used were elderly people who had been diagnosed with hypertension ≥ 1 year and lived with their families, while the exclusion criteria were elderly people who moved, refused to be respondents, and lived alone. The instruments used were family support questionnaire sheets and compliance variables using MMAS-8. The questionnaire has been tested for validity and reliability, the data analysis used was univariate and bivariate. Results: Data analysis showed emotional support (p-value = 0.012), instrumental (p-value = 0.037), informational (p-value = 0.026), and appreciation (p-value = 0.028). All family support variables obtained p-values ​​<0.05, so there is a significant influence between family support on elderly compliance in undergoing hypertension treatment. Conclusion: There is a significant relationship between emotional, instrumental, informational, and appreciation support variables from the family on elderly compliance in undergoing hypertension treatment. Suggestion: Community health centers should provide counseling regarding emotional, instrumental, informational, and appreciation support to families, so that the elderly feel comfortable, close to their families, and receive affection, empathy, and trust from their families. Keywords: Compliance; Elderly; Family Support; Hypertension. Pendahuluan: Hipertensi merupakan suatu gangguan pada pembuluh darah yang mengakibatkan suplai oksigen dan nutrisi yang dibawa oleh darah terhambat sampai kejaringan tubuh yang membutuhkannya. Dukungan keluarga adalah sikap, tindakan, penerimaan keluarga terhadap anggota keluarganya yang berupa dukungan emosional, dukungan instrumental, dukungan informasional dan dukungan penghargaan. Tujuan: Untuk menganalisis dukungan keluarga (etnis Batak Toba) terhadap kepatuhan lansia penderita hipertensi dalam menjalani pengobatan. Metode: Penelitian kuantitatif dengan pendekatan cross sectional, dilakukan kepada masyarakat Batak Toba di wilayah kerja UPT Puskesmas Uluan sebanyak 64 pasien dan Janji Matogu sebanyak 76 pasien pada bulan Februari-Maret 2024 kepada 140 sampel. Pengumpulan data menggunakan teknik non probability sampling yaitu purposive sampling dan rumus Slovin untuk tingkat kesalahan 5%. Kriteria inklusi sampel yang digunakan adalah lansia yang telah didiagnosa hipertensi ≥ 1 tahun dan tinggal dengan keluarga, sedangkan kriteria eksklusi yaitu lansia yang berpindah-pindah tempat tinggal, menolak menjadi responden, dan tinggal sendiri. Instrumen yang digunakan yaitu lembar kuesioner dukungan keluarga dan variabel kepatuhan menggunakan MMAS-8. Kuesioner tersebut telah diuji validitas dan reliabilitas, analisis data yang digunakan yaitu univariat dan bivariat. Hasil: Analisis data menunjukkan dukungan emosional (p-value = 0.012), instrumental (p-value = 0.037), informasional (p-value = 0.026), dan penghargaan (p-value = 0.028). Seluruh variabel dukungan keluarga mendapatkan p-value <0.05, sehingga terdapat pengaruh yang signifikan antara dukungan keluarga terhadap kepatuhan lansia menjalankan pengobatan hipertensi. Simpulan: Ada hubungan yang signifikan antara variabel dukungan emosional, instrumental, informasional, dan penghargaan dari keluarga terhadap kepatuhan lansia yang menjalani pengobatan hipertensi. Saran: Pihak puskesmas memberikan penyuluhan mengenai dukungan emosional, instrumental, informasional, dan penghargaan kepada keluarga, sehingga lansia merasa nyaman, dekat dengan keluarga, serta mendapatkan kasih sayang, empati, dan kepercayaan dari keluarga. Kata Kunci: Dukungan Keluarga; Hipertensi; Kepatuhan; Lansia.